Testing of a new way of cadastral maps renewal in Slovakia - Kyseľ, Peter (Geodetski vestnik, 2022)
One of the biggest problems in the Slovak cadastre is the quality of maps. Approximately half of them require a new mapping. The quality of the other half is also not high, and they include local shifts. The paper deals with a proposal for a new way of their renewal—Cadastral Operate Renewal by Correction (RbC). This process is based on a transformation of the part of the map with local shifts using a new GNSS measurement. The process has three main stages—homogeneity analysis, transformation, and final control. The result of the RbC process is a renewed cadastral map without any local shifts. Another goal of this paper is to test this process in a chosen cadastral unit and to analyse the results. If the testing is successful, this process could be a fast and cheap alternative to a new mapping in case of these cadastral maps with local shifts.
Keywords: homogenost načrta; katastrski načrti; lokalni premiki; obnavljanje; Slovaška; transformacija